Mental Health of Nurses Employed in Surgical and Non-invasive Treatment Wards - Anna Skuzińska (Pielęgniarstwo Neurologiczne i Neurochirurgiczne)
Introduction. The nursing profession requires employees to be highly resistant to stress. Assisting patients in their experience of pain, illness, helplessness is a stressful experience can be a traumatic experience especially in the face of an immediate threat to a patient’s life. Nursing staff working in treatment wards is exposed to particularly intense stress, in contact with a patient experiencing fear of a surgery and a patient after a surgery experiencing postoperative pain and requiring specialist care.